EFFECT OF ZAKAT, INFAK AND SEDEKAH (ZIS), INDEX HUMAN DEVELOPMENT (HDI) AND UNEMPLOYMENT ON INDONESIAN ECONOMIC GROWTH AT 2013-2017 - Agus Arwani; Anis Wahdati (Al-Tijary, 2020)
Islamic view that growth in the economy is not only oriented to create accretion of single production but indicated the basis of the fairness of distribution, one of them with equal distribution of income that did not create a gap between the rich and the poor. In its development, many factors influence the economic growth, Including Zakat Infak and Sedekah (ZIS), Human Development Index, and Unemployment rate. The research type is explanatory with a quantitative approach. The type of data used is secondary data and Analysed using multiple linear regression by using Software Eviews 10. The results of the study have demonstrated that Zakat Infak and Sedekah (ZIS) and the Human Development Index (HUMAN DEVELOPMENT INDEX) influence positively and significantly on Indonesia's economic growth in 2013-2017. While unemployment did not affect. Based on the F-test, variable Zakat Infak and Sedekah (ZIS), the Human Development Index (HUMAN DEVELOPMENT INDEX), and unemployment simultaneously affected the Indonesia’s Economic growth . The magnitude of the effect of independent variables on the dependent variable amounted to 41.1%, while 58.9% are influenced by variables other research.